Istanbul Protocol implementation in Central Asia: Bending the arc of the moral universe. (January 2020) - Iacopino, Vincent; Haar, Rohini J.; Heisler, Michele; Beriashvili, Rusudan
Abstract: In countries emerging from authoritarian rule, a major challenge is ending often widespread and systematic torture and ill-treatment practices. Between 2011 and 2019, Physicians for Human Rights (PHR), in collaboration with the Open Society Foundation (OSF), the Open Society Justice Initiative (OSJI) and regional and local partners, worked to establish effective torture investigation and documentation practices in the Central Asian countries of Kyrgyzstan, Tajikistan, and Kazakhstan. Our approach consisted of activities in three sequential phases – (1) assessment, (2) capacity building, and (3) policy reform. In this paper, we briefly describe activities during each phase and identify key lessons learned from these experiences and resulting policy and program reforms as a model for future efforts in other settings. Highlights: National efforts to implement the Istanbul Protocol (IP) standards provide important lessons. Key phases were assessment, capacity building, and policy reforms. Key lessons from activities in each of these phases are delineated. Continued challenges to create mechanisms to eliminate torture are described.